2019
DOI: 10.1136/bmjresp-2018-000357
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis in the UK: insights from British Thoracic Society registry data

Abstract: IntroductionThe British Thoracic Society Sarcoidosis Registry allows physicians to record clinical data after gaining written consent from patients. The registry’s aim is to phenotype sarcoidosis in the UK.MethodsBetween February 2013 and July 2017, demographic details for 308 patients (with complete clinical data for 205 patients) presenting to 24 UK hospitals were recorded. This data was analysed to detail methods of presentation, diagnosis and management.ResultsFatigue was a significant complaint, affecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
3
14
1
Order By: Relevance
“…Four in ten patients with sarcoidosis received at least one prescription of systemic corticosteroids around the time of diagnosis, whereas second line (steroid-sparing) treatments were rarely prescribed at diagnosis. These observations are consistent with reports from the United States, the United Kingdom, Spain, and Poland [19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 93%
“…Four in ten patients with sarcoidosis received at least one prescription of systemic corticosteroids around the time of diagnosis, whereas second line (steroid-sparing) treatments were rarely prescribed at diagnosis. These observations are consistent with reports from the United States, the United Kingdom, Spain, and Poland [19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 93%
“…Analysis of the British Thoracic Society Sarcoidosis Registry showed that 8% of all patients with pulmonary sarcoidosis were prescribed inhaled steroids (94). Although an obstructive defect is present in almost a quarter of UK patients with sarcoidosis (95), there is no evidence for inhaler efficacy (96).…”
Section: Steroid Regimensmentioning
confidence: 99%
“…2000) Not published Not published United States RAPID (NCT03297775) June 2017 - current RA and ILD inc. IPF (Est. 500) Not published Not published International EUSTAR [ 27 ] June 2004 - current SSc inc. SSc-ILD (> 15,000) 92.2 (±21.3) 68.3 (±21.1) Australia SASR [ 28 ] 1993–2007 Scleroderma (786) Not published Not published UK BRILL [ 29 ] 1987 - current RA and ILD (230) 101 (54–145) b 70 (44–117) c 61 (33–106) b 52 (22–109) c UK BTS [ 30 ] Feb 2013 - current Sarcoidosis (> 300) 97 78.2 Europe eurIPFreg (NCT02951416) Sept 2009 - current ILDs inc. IPF (> 1080) Not published Not published Abbreviations : AILDR Australasian ILD registry, CARE-PF The Canadian Registry for Pulmonary Fibrosis, PFF-PR Pulmonary Fibrosis Foundation Patient Registry, REGIS Romanian Registry for Interstitial Lung Diseases, UIP Usual Interstitial Pneumonia, RIPID Registry of Diffuse Infiltrative Pulmonary Diseases, RAPID Rheumatoid Arthritis patients at Risk for ILD, RA Rheumatoid Arthritis, EUSTAR European Scleroderma Trials and Research Group, SSc Systemic Sclerosis, SASR South Australia Scleroderma Register, BRILL British Rheumatoid Interstitial Lung network, BTS British Thoracic Society a Trial identifier where available b Limited disease on CT c Extensive disease on CT …”
Section: Discussionmentioning
confidence: 99%